Catalytic conversion of ethanol to biojet over zeolite catalysts - Thainoi, Suwimon; Kijsiri, Phattraphorn; Ausavasukhi, Artit (KKU Science Journal, 2020)
Biojet can be produced from ethanol obtained by fermentation process via dehydration and other reactions as green alternative routes. HZSM-5 zeolite showed high activity in the conversion of ethanol to biojet, while other zeolites (HBeta, HMordenite, and HY) mainly formed ethylene. The HZSM-5 with a lower Si/Al ratio (high acid density) provided more biojet selectivity. Reaction temperature, W/F and ethanol concentration have a significant effect on the product distribution and catalytic activity. The optimum reaction conditions on the best catalyst (HZSM-5(11)) were found as follows; reaction temperature of 450 oC, W/F of 21.12 minutes and ethanol concentration of 99.5 % (v/v). Under such conditions, the selectivity of biojet was 43.77%. Generally, HZSM-5 zeolite can deactivate due to coke formation. After the catalyst regeneration, both the ethanol conversion and biojet selectivity were still maintained.